Antibacterial activity of Myrtus communis leaf extract against three pathogenic Xylella fastidiosa subspecies - Incampo, Giuseppe; Mourou, Marwa; Cornacchia, Davide; Montilon, Vito; Difonzo, Graziana; Montoro, Paola; Caponio, Francesco; Faretra, Francesco; Nigro, Franco; Pollastro, Stefania (Frontiers in Plant Science, 2025)
The limited availability of sustainable strategies for managing Xylella fastidiosa (Xf) underscores the urgent need for innovative and practical antimicrobial solutions. In this study, an extract from the leaves of Myrtus communis (MC) biotype “Tarantino”, known for its antibacterial properties, was evaluated in vitro using well diffusion and broth dilution assays against X. fastidiosa subsp. pauca (Xfp), multiplex (Xfm), and fastidiosa (Xff), all of which have been reported in Europe and in the Apulia region. Prior to biological testing, the MC leaf extract (MCLE) underwent chemical characterization via LC-Q-Exactive-Orbitrap/MS and LC-Q-Exactive-Orbitrap/MS/MS. Metabolite profiling revealed the presence of several phenolic acids, flavonol derivatives, and ellagitannins. In the in vitro assays, MCLE exhibited clear inhibition zones against all three Xf subspecies, with diameters ranging from 4.8 to 22.6 mm compared to the control. Additionally, in broth cultures, a 1:5 dilution of MCLE significantly inhibited bacterial growth, resulting in 65%, 86%, and 66% inhibition for Xfp, Xfm, and Xff, respectively. For in planta assays, symptom severity on the canopy of Nicotiana benthamiana was notably reduced in plants treated with MCLE compared to those inoculated with Xf alone. Quantitative real-time PCR confirmed the efficacy of MCLE: untreated, inoculated plants exhibited significantly lower Cq values (F = 120; p < 0.001), indicating higher bacterial loads compared to MCLE-treated plants. Overall, this study highlights the potential of MC-based formulations as promising, eco-friendly tools for the management of Xf-related diseases, meriting further validation under field conditions.